2014
DOI: 10.1073/pnas.1316181111
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous selection by object-based attention in visual and frontal cortex

Abstract: Models of visual attention hold that top-down signals from frontal cortex influence information processing in visual cortex. It is unknown whether situations exist in which visual cortex actively participates in attentional selection. To investigate this question, we simultaneously recorded neuronal activity in the frontal eye fields (FEF) and primary visual cortex (V1) during a curve-tracing task in which attention shifts are object-based. We found that accurate performance was associated with similar latenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
66
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 45 publications
7
66
1
Order By: Relevance
“…If the monkeys made an error and chose the wrong curve, the erroneously selected curve elicited extra activity, both in V1 and in the frontal eye fields. However, now selection in frontal cortex preceded selection in visual cortex as if the frontal cortex imposed its erroneous decision onto visual cortex [13 ]. In addition, the authors observed correlations between frontal and visual cortex that were strongest for the attended curve.…”
Section: Visual Neurons Are Modulated By 'Top-down' Phenomena At Precmentioning
confidence: 94%
See 2 more Smart Citations
“…If the monkeys made an error and chose the wrong curve, the erroneously selected curve elicited extra activity, both in V1 and in the frontal eye fields. However, now selection in frontal cortex preceded selection in visual cortex as if the frontal cortex imposed its erroneous decision onto visual cortex [13 ]. In addition, the authors observed correlations between frontal and visual cortex that were strongest for the attended curve.…”
Section: Visual Neurons Are Modulated By 'Top-down' Phenomena At Precmentioning
confidence: 94%
“…One example task associated with attention shifts is curve-tracing ( [13 ], Figure 1b). The authors of this study required monkeys to mentally trace a curve that starts at a fixation point to determine the endpoint of this curve, because the circle at the end was the target for an eye movement.…”
Section: Visual Neurons Are Modulated By 'Top-down' Phenomena At Precmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies have focused on the FEF and areas in the back of the brain, and the task design and measurement method used vary widely from study to study. Every study has found that when the target is more difficult to locate, neurons in the FEF and in the dorsolateral PFC (dlPFC) signal its location either before or as early as neurons in occipital, parietal, and temporal areas do , Cohen et al 2009a, Monosov et al 2010, Zhou & Desimone 2011, Gregoriou et al 2012, Ibos et al 2013, Pooresmaeili et al 2014). This conclusion is based on chronological comparison of not only single-unit modulation times but also intracortical local field potentials and the N2pc event-related potential (ERP), which is identified with the allocation of visual attention .…”
Section: Visual Processing Remapping and Target Selectionmentioning
confidence: 99%
“…First, studies have consistently shown that attention increases the spike rates of neurons encoding attended stimuli compared to non-attended stimuli (Desimone and Duncan, 1995). The effect on firing rates has been observed in many, if not all, areas of the cerebral cortex, ranging from primary visual cortex to areas of the frontal cortex (Pooresmaeili et al, 2014). Second, attention makes neural responses more reliable.…”
mentioning
confidence: 99%